Antibacterial and antibiofilm activities of protocatechualdehyde and its synergy with ampicillin against methicillin-resistant Staphylococcus aureus - Wang, Ying; Liu, Xiaojing; Song, Lin; Chen, Kun; Shi, Chao; Peng, Chuantao; Yang, Qingli; Li, Zhaojie (Frontiers in Microbiology, 2024)
Protocatechualdehyde (PA) is a phenolic acid present in many plants and has many biological activities. Herein, the antagonistic effects and the action mechanism of PA against methicillin-resistant Staphylococcus aureus (MRSA) were studied. The results showed that PA had both significant antibacterial and anti-biofilm activities against MRSA. Additionally, PA had synergy with ampicillin against MRSA. It was elucidated that PA was prominent in destroying cell membranes, increasing cell membrane permeability and intracellular ROS production, thus leading to bacterial cell damage. Transcriptome analysis showed that PA disrupts many physiological pathways, including increasing cell membrane permeability, inhibiting biofilm formation, decreasing resistance to antimicrobial agents, and impairing DNA replication. Finally, the antimicrobial preservation test showed that PA could inhibit the growth of MRSA and prevent the corruption of beef. In summary, PA is an effective natural antibacterial substance and has a good application potential in food preservation, even in tackling antibiotic resistance problems.